2019
DOI: 10.1097/ico.0000000000002171
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Early Sjögren Markers and Symptoms and Signs of Dry Eye

Abstract: Purpose: Animal models suggest that early markers of Sjögren syndrome (EMS)—antibodies against salivary protein 1, parotid secretory protein, and carbonic anhydrase 6 (CA6)—are more accurate signals of early Sjögren when compared with classic markers (anti-Ro and anti-La). To further understand the relationship between EMS and dry eye (DE), we compared symptoms and signs of DE in subjects who tested positive versus negative for EMS. Methods: In this cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Cases included individuals with DE symptoms and/or signs, who had pSS as defined by the 2016 American College of Rheumatology criteria 15 [total weighted score of $4: 1) anti-SSA/ Ro and anti-SSB/La antibody positivity; focal lymphocytic sialadenitis with a focus score $1 foci/4 mm 2 , each scoring 3; 2) ocular staining score of $5; Schirmer #5 mm/5 minutes; unstimulated salivary flow rate of #0.1 mL/min, each scoring 1, n = 1] or had an elevation of at least 1 of 9 early SS markers (IgM, IgA, or IgG antibodies against SP1 (n = 5), PSP (n = 7), or CA6 (n = 13) at a level of 20 EU/mL or greater, n = 19). 13 In this study, 12 cases had 1 elevated early SS marker, 6 cases had 2 elevated markers, and 1 case had 4 elevated markers. Controls included age-matched and sex-matched individuals without DE symptoms or signs, including tear breakup time (TBUT) $5 seconds, corneal staining score #2, and Schirmer score $5 mm in both eyes.…”
Section: Study Populationmentioning
confidence: 49%
See 1 more Smart Citation
“…Cases included individuals with DE symptoms and/or signs, who had pSS as defined by the 2016 American College of Rheumatology criteria 15 [total weighted score of $4: 1) anti-SSA/ Ro and anti-SSB/La antibody positivity; focal lymphocytic sialadenitis with a focus score $1 foci/4 mm 2 , each scoring 3; 2) ocular staining score of $5; Schirmer #5 mm/5 minutes; unstimulated salivary flow rate of #0.1 mL/min, each scoring 1, n = 1] or had an elevation of at least 1 of 9 early SS markers (IgM, IgA, or IgG antibodies against SP1 (n = 5), PSP (n = 7), or CA6 (n = 13) at a level of 20 EU/mL or greater, n = 19). 13 In this study, 12 cases had 1 elevated early SS marker, 6 cases had 2 elevated markers, and 1 case had 4 elevated markers. Controls included age-matched and sex-matched individuals without DE symptoms or signs, including tear breakup time (TBUT) $5 seconds, corneal staining score #2, and Schirmer score $5 mm in both eyes.…”
Section: Study Populationmentioning
confidence: 49%
“…12 In fact, early marker positivity is more common than late marker positivity (antibodies to Ro and La) in individuals with DE, found in up to 73% of individuals with DE symptoms and suggestive clinical signs (eg, aqueous tear deficiency or ocular surface inflammation). 13…”
mentioning
confidence: 99%
“…The latter study showed an association of eSjA with severe sicca symptoms, but eSjA did not differentiate SS-dry eye from non-SS dry eye. Similarly, anti-CA6 was most frequently elevated in patients with dry eye condition and a clinical suspicion of SS when a defined population of US veterans in Miami was screened (52). There were no demographic or comorbidity differences between eSjA-positive and eSjA-negative subjects, and eSjA did not correlate with more severe tear film measures.…”
Section: Discussionmentioning
confidence: 87%
“…This may be due to differences in the study population, with adolescents likely to be more adept at accessing information from the internet. In addition, adolescents might have subjective symptoms of DED but do not meet the actual diagnostic criteria for field epidemiological studies ( 40 , 41 ). The frequency analysis of hot words related to DED mainly includes three aspects: other associated ocular diseases, treatment options and the subjective symptoms of patients.…”
Section: Discussionmentioning
confidence: 99%